2022
DOI: 10.1186/s40337-022-00534-9
|View full text |Cite
|
Sign up to set email alerts
|

Complex functional brain network properties in anorexia nervosa

Abstract: Background Anorexia nervosa (AN) is a disorder characterized by an incapacitating fear of weight gain and by a disturbance in the way the body is experienced, facets that motivate dangerous weight loss behaviors. Multimodal neuroimaging studies highlight atypical neural activity in brain networks involved in interoceptive awareness and reward processing. Methods The current study used resting-state neuroimaging to model the architecture of large-sc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…However, these alterations involve a number of disturbances in the interplay of several different stress-responsive systems that interact centrally and peripherally to produce individualized clinical phenotypes and vulnerabilities. Alterations in functional connectivity have been investigated in separate studies of both PTSD [ 279 282 ] and ED patients [ 283 286 ]. No such studies have yet been reported in ED patients with and without PTSD.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these alterations involve a number of disturbances in the interplay of several different stress-responsive systems that interact centrally and peripherally to produce individualized clinical phenotypes and vulnerabilities. Alterations in functional connectivity have been investigated in separate studies of both PTSD [ 279 282 ] and ED patients [ 283 286 ]. No such studies have yet been reported in ED patients with and without PTSD.…”
Section: Methodsmentioning
confidence: 99%
“…Alterations in functional connectivity have been investigated in separate studies of both PTSD [ 279 282 ] and ED patients [ 283 286 ]. No such studies have yet been reported in ED patients with and without PTSD.…”
Section: Methodsmentioning
confidence: 99%
“…The caudate which is part of the striatum and connected to the substantia nigra is heavily involved in the reward system where the dopaminergic neurons are produced [69]. Changes in caudate volume have been found to be associated with disorders such as anorexia and Parkinson's disease [70], [71] and our results point to TXNDC12 being the mediator of these associations via the dopaminergic neuron generation and reward system. Some of the proteins we identified had an established role in brain development.…”
Section: Discussionmentioning
confidence: 55%
“…Betweenness centrality describes degree to which a brain region lies on the shortest path between two other regions. Acting as way stations, regions with high betweenness centrality are topologically primed to control communication between other regions 38 . Eigenvector centrality reflects how connected a given brain region is to other brain regions with high centrality (greater number of fiber tracts) and is a measure of a region’s overall influence on the network 39 .…”
Section: Methodsmentioning
confidence: 99%